Synergistic therapy for diabetic retinopathy via dual blockade of VEGF-A and TNF-α with a bispecific nanobody - Wu, Chenlu; Shen, Yue; Xu, Chengnan; Bi, Chong; Yan, Chenyue; Niu, Jinping; Zheng, Wenyun; Ma, Xingyuan (Frontiers in Pharmacology, 2026)
IntroductionAnti-vascular endothelial growth factor (VEGF) therapy fails in approximately 30% of diabetic retinopathy (DR) patients, indicating the limitations of solely targeting VEGF-A. This study aimed to design a bispecific nanobody, Nb-TV, targeting both tumor necrosis factor-α (TNF-α) and VEGF-A to achieve dual anti-inflammatory and anti-angiogenic effects for potential DR treatment.MethodsThe inhibitory effects of Nb-TV were evaluated in vitro using adult retinal pigment epithelium-19 (ARPE-19) cells and human umbilical vein endothelial cells (HUVECs). Key assays included analysis of nuclear translocation (p65, p38α), phosphorylation (Erk1/2), expression of inflammatory factors (IL-6, IL-8, MCP-1) and inducible nitric oxide synthase (iNOS), Caspase-1 activation, and assessments of HUVEC proliferation, migration, and tube formation. The in vivo therapeutic efficacy was investigated in a DR mouse model, where Nb-TV was administered via eye drops. Retinal levels of TNF-α and VEGF-A, neovascularization, and structural lesions were examined.ResultsIn vitro, Nb-TV inhibited over 60% of TNF-α-induced p65 nuclear translocation in ARPE-19 cells, significantly reducing IL-6, IL-8, and MCP-1 expression by 24.6%, 26.6%, and 37.8%, respectively, and suppressing Caspase-1 activation. In HUVECs, it effectively blocked VEGF-A-driven proliferation, migration, and tube formation by inhibiting p38α nuclear translocation (28.5% reduction) and Erk1/2 phosphorylation (98.6% inhibition), while downregulating iNOS expression. In vivo, topical Nb-TV application decreased TNF-α and VEGF-A levels in retinal tissues of DR mice, controlled pathological neovascularization, and improved retinal structural damage.DiscussionOur findings demonstrate that Nb-TV mechanistically dual-targets the TNF-α/NF-κB and VEGF-A/MAPK pathways, mitigating both inflammation and angiogenesis synergistically. This validates Nb-TV as a novel bispecific nanobody with promising therapeutic potential for DR by simultaneously modulating key pathological pathways. This study not only proposes a strategic approach for refractory DR but also provides a framework for targeting other multifactorial ocular and systemic diseases.